A escola, os professores e a inovação educacional - Zanata, Eliana Marques [UNESP]; Marques, Antonio Francisco [UNESP] (My University, 2014)
The purpose of this essay is to reflect on the quality of the school and psychosocial aspects involved in the assimilation of educational innovations by teachers in their teaching practices.Innovations cause resistance which endanger the goals of improving education outcomes. This makes the possibilities of basic schooling fail, preventing contribute to the transformation of living conditions of the working classes.

Este estudo tem como objetivo refletir sobre a qualidade da escola e aspectos psicossociais envolvidos na assimilação de inovações educacionais pelos professores nas suas práticas pedagógicas. As inovações, em geral, suscitam resistências que colocam em risco os objetivos de melhoria dos resultados do ensino, sobretudo, levando ao fracasso as possibilidades da escolarização básica contribuir para as transformações das condições de vida das classes populares.
Keywords: Educational innovation; Social transformation; Resistance to change; Inovação educacional; Transformação social; Resistência a mudança